STRATEGI PENGEMBANGAN KAWASAN OBJEK WISATA CANDI MUARA TAKUS - Pislawati SE.,M.Si (STIA Indragiri, 2019)
Abstract: Regional Development Strategy of Muara Takus Temple Tourism Object. This study aims to determine the strategy of the development of Muara Takus Temple tourist attraction area conducted by the Department of Tourism, Youth and Sports. The research informant is Head of Kasi in the field of tourism business development, BPCB, chairman of GERNASTA, cultural and community figures and visitors of snowbell sampling withdrawal technique. Technique of collecting data is done by interview, observation, and documentation. Data analysis using triangulation method. The results showed that the strategy in the development of Muara Takus temple object area can not be implemented properly, because there are various obstacles that are so significant that affect the success of the strategy set by the Department of Tourism, Youth and Sports before.Keywords: strategy, development, tourism object